2021
DOI: 10.1155/2021/1676269
|View full text |Cite
|
Sign up to set email alerts
|

Study on Optimization of Delay Method of Wedge Cut Blasting in Tunnel

Abstract: Relying on the entrance section of a high-speed railway tunnel blasting project, the fluid-solid coupling algorithm based on ANSYS/LS-DYNA was used to optimize the parameters of wedge cut blasting, and the vibration could be reduced on the basis of ensuring the blasting effect. Through the combination of visual numerical simulation results and rock-breaking mechanism of wedge cut blasting, the maximum vibration velocity of different monitoring points in the model under different segmented time delay was analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…For the other two materials, because the rock blasting process always involves a rapid increase in strain, the rock mass was modeled by the *MAT_PLASTIC_KINEMATIC constitutive model considering the strain rate effect 50 . Then, the *MAT_DRUCKER_PRAGER constitutive model was employed to depict the great deformation of the stemming plug under strong dynamic loads 51 . In addition to the material parameters of rocks from laboratory tests, the parameters of other materials were taken from previous studies and are provided in Tables 1 , 2 , 3 , 4 .…”
Section: Finite Element Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…For the other two materials, because the rock blasting process always involves a rapid increase in strain, the rock mass was modeled by the *MAT_PLASTIC_KINEMATIC constitutive model considering the strain rate effect 50 . Then, the *MAT_DRUCKER_PRAGER constitutive model was employed to depict the great deformation of the stemming plug under strong dynamic loads 51 . In addition to the material parameters of rocks from laboratory tests, the parameters of other materials were taken from previous studies and are provided in Tables 1 , 2 , 3 , 4 .…”
Section: Finite Element Simulationmentioning
confidence: 99%
“…Through similar material model experiments, Yang et al 20 researched the effect of the cutting hole angle on the rock block size and cavity morphology parameters of wedge cutting blasting and further provided a rational range of cutting hole angles. Gao et al 21 numerically studied the influence law of the initiation mode of the cutting holes on the damage distribution within the cutting cavity. They concluded that the staggered arrangement of the initiation points in the left and right cutting holes was the most reasonable mode.…”
Section: Introductionmentioning
confidence: 99%
“…In order to control the tunnel blast, measures such as shortening the individual cycle of excavation, opening up the exterior in stages, adjusting the hole sizes incrementally, and reducing the maximum section charge of dynamite used are often adopted [9][10][11]. In recent years, research into controlled blasting has made fruitful progress [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%